Interpolation by Splines of Even Degree According to Subbotin and Marsden - Volkov, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We consider the problem of interpolation by splines of even degree according to Subbotin and Marsden. The study is based on the representation of spline derivatives in the bases of normalized and nonnormalized B-splines. The systems of equations for the coefficients of these representations are obtained. The estimations of the derivatives of the error function in the approximation of an interpolated function by the complete spline are deduced via the norms of inverse matrices of the investigated systems of equations. The relationship between the splines in a sense of Subbotin and the splines in a sense of Marsden is established.